B-A Chromosome Translocations Possessing an A Centromere Partly Overcome the Root-Restricted Process of Chromosome Elimination in Aegilops speltoides - Li, Daiyan; Ruban, Alevtina; Fuchs, Jörg; Kang, Houyang; Houben, Andreas (Frontiers in Cell and Developmental Biology, 2022)
Some eukaryotes exhibit dramatic genome size differences between cells of different organs, resulting from the programmed elimination of chromosomes. Aegilops speltoides is an annual diploid species from the Poaceae family, with a maximum number of eight B chromosomes (Bs) in addition to its inherent seven pairs of standard A chromosomes (As). The Bs of this species undergo precise elimination in roots early in embryo development. In areal parts of the plant, the number of Bs is stable. To affect the root restricted process of B chromosome elimination, we employed X-ray mutagenesis, and different types of restructured Bs were identified. Standard Bs were observed in all analyzed shoots of mutagenized plants, while B-A translocations were only observed in 35.7% of F1 plants. In total 40 different B variants inconsistently escaped the elimination process in roots. As a result, mosaicism of B chromosome variants was found in roots. Only a small B chromosome fragment fused to an A chromosome was stably maintained in roots and shoots across different generations. The absence of B-A translocation chromosomes possessing a derived B centromere in root cells implies that the centromere of the B is a key component of the chromosome elimination process.